Analyzing Sustainable Development in Indonesia Based on Environmental Kuznet Curve - Yanuarti, Wella Amalia; Rachmawati, Lucky (Universitas Negeri Semarang, 2024)
Sustainable development is long term development with economic, social, and environmental aspects. Development in Indonesia is a trade off in which an increase in income will increase degradasi environemntal. This research use the EKC theory that connects aspects of economic growth to the environment represented by CO2. The VECM analysis technique is used to see the cointegration of short and long term relationships. In the short term it show that GDP, GDP2 has significant effect on CO2, while HDI has no effect. The results of this studi show that EKC curve is rejected in a U-shape so that sustainable development is weak. In the long term GDP, GDP2, and HDI have significat effect on CO2. The result of the show support for the EKC theory with an inverted U-shaped curve in the long run so that sustainable development is strong. It show that Indonesia is a country whose economic growth depends on energy consumption. This study provides an overview of government policies to reduce carbon dioxide gas with a tax holidays for FDI to encourage green industries, encourage renewable energy sources. Within the scope of education provides an environment-based learning curriculum.